2006
DOI: 10.1111/j.1745-7262.2006.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

The cavernoso-anal reflex: response of the anal sphincters to cavernosus muscles' stimulation

Abstract: Cavernosus muscles' contraction is suggested to evoke anal sphincteric contraction, which seems to be a reflex and mediated through the "Cavernoso-anal reflex". Anal sphincteric contraction during coitus presumably acts to close the anal canal to thwart flatus or fecal leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In fact, the UM motoneurons have been found bilaterally in a roundish nucleus located laterally to the central canal of the SC S1–S2 segments, in a intermedio‐lateral area (Gazza et al, ). However, the site of the pig ICM somatic motor neurons, extending from the base of the ventral horn, allowed us to hypothesize a close topographic correlation with UM‐projecting motoneurons, supporting the hypothesis that the ICM contraction could influence also the activity of the urethral sphincter (Shafik et al, b). This functional relation could be due to spinal interneurons projecting to the striated perineal muscles, whose presence has been documented in the rat SC dorsal gray commissure (Holstege, ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In fact, the UM motoneurons have been found bilaterally in a roundish nucleus located laterally to the central canal of the SC S1–S2 segments, in a intermedio‐lateral area (Gazza et al, ). However, the site of the pig ICM somatic motor neurons, extending from the base of the ventral horn, allowed us to hypothesize a close topographic correlation with UM‐projecting motoneurons, supporting the hypothesis that the ICM contraction could influence also the activity of the urethral sphincter (Shafik et al, b). This functional relation could be due to spinal interneurons projecting to the striated perineal muscles, whose presence has been documented in the rat SC dorsal gray commissure (Holstege, ).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, during skeletal muscle contraction it is possible to observe a local functional vasodilation to promote the extraction of oxygen and nutrients from the blood (Van Teeffelen and Segal, 2003), rapidly followed by a sympathetic vasoconstriction (Thomas and Segal, ) to increase and preserve the local pressure. In particular it has also been demonstrated that the intermittent ICM contraction during rigid erection provide a natural mechanism that keeps the cavernous tissue well oxygenated and prevents its distruction by ischemia (Shafik et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraction of the cavernosus muscle that is activated during intercourse (20,21) may evoke sphincter contraction via the "cavernoso-anal reflex" (22). Consequently, anal sphincter contraction during coitus may contribute to the closing of the anal canal, to guard against flatus or feces ( 22).…”
Section: External Anal Sphinctermentioning
confidence: 99%